Effect of Business Capital, Characteristics, Motivation and Entrepreneurs Innovation on Performance UMKM Tempe in Mataram City - Maulida, Elita; Darmawan, Dwi Putra; Arisena, Gede Mekse Korri (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen AgribisnisDO - 10.24843/JMA.2023.v11.i01.p07, 2023)
UMKM are one of the business units that are able to contribute to economic growth. Enterprises, micro, small and medium enterprises (UMKM tempe in the city of Mataram became one of the dominant industrial centers. The purpose of this study was to (a) analyze the business capital, characteristics, motivation and entrepreneurial innovation of tempeh UMKM in Mataram City; (b) analyzing the performance of tempeh UMKM in Mataram City; (c) analyze the effect of venture capital, characteristics, motivation and entrepreneurial innovation on the performance of tempeh SMEs in Mataram City. The sampling technique used is proportional random sampling, with the selection of 145 respondents. This research was conducted in the city of Mataram on tempeh UMKM. The location selection was determined by purposive sampling. The data analysis used is a qualitative method and by using a structural equation model (SEM). The results of the study indicate that (a) Business capital, characteristics, motivation and entrepreneurial innovation in Mataram City have been assessed as good seen from the respondents' responses which are dominated by "good" and from each variable indicator; (b) the performance variable of Tempe UMKM has been assessed as good, seen from the respondents' responses which are dominated by "agree" and from each variable indicator; (c) Business capital, characteristics, motivation and innovation in Mataram City have a significant effect on the performance of Tempe UMKM indirectly, where the variables that have a significant effect are business capital of 2,096, entrepreneurial characteristics of 3,407, while motivation of 2,416, and tempe innovation of 2,556 So it can be concluded that it has a positive effect. Suggestions in this study are for the success of the tempe-making business, courage is needed in business capital so that motivation will arise as a driving force to carry out an activity or effort to achieve goals in entrepreneurship.